2014
DOI: 10.1590/0001-37652014109112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on the nutritional quality of Agaricus bisporus strains cultivated in different composts

Abstract: The effect of irradiation doses (0, 125, 250 and 500 Gy) on the nutritional quality of A. bisporus mushrooms (strains ABI-07/06, ABI-05/03 and PB-1) cultivated in composts based on oat straw (Avena sativa) and brachiaria (Brachiaria sp.) was evaluated. The experimental design was 4 x 3 x 2 factorial scheme (irradiation doses x strains x composts), with 24 treatments, consisting of two repetitions each, totaling 48 experimental units (samples of mushrooms). The samples were irradiated in Cobalt-60 irradiator, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to Singh and Jha, the four phases of composting include: [1]. Mesophilic phase; [2]. Thermophilic phase; [3].…”
Section: Phases Of Compostingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Singh and Jha, the four phases of composting include: [1]. Mesophilic phase; [2]. Thermophilic phase; [3].…”
Section: Phases Of Compostingmentioning
confidence: 99%
“…The nutritional value of edible mushroom and the bioactive compounds they contain, make mushrooms a healthy food (Andrade et al, 2014). Medicinal significance and dietary nature of white button mushroom is well documented (Keleş et al, 2011;Changizi et al, 2012;Muszynska et al, 2017, Verma et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Some food constituents have been shown to be vulnerable to destruction by ionizing radiation. Andrade et al (2014) demonstrated that food composition of mushrooms was affected by gamma irradiation, in particular the dose of 500 Gy, which granted to highest average of fiber and crude protein in the mushrooms. Similarly, Bamidele and Akanbi (2013) reported that gamma irradiation has significant effect on the amino acids profile, but no significant effect on minerals and vitamins content of the pigeon pea flour.…”
Section: Introductionmentioning
confidence: 99%